SENI: ANTARA BENTUK DAN ISI - Sabatari, Widyabakti (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
When a new art work is created, it usually causes the emergence of new definitions of art, which are based on different points of view and interpretations. Therefore, it is difficult to give an ideal definition of art. The scope of art is so wide and the facet is so various that art has plural meanings. There are always incomplete and incomprehensive views of art. There are also many different branches of art. On account of its wide scope, the philosophy of art is badly needed as a way to comprehend and analyze matters related to art and its definitions. Based on a view that there is no difference between art and beauty, every beautiful thing is an art and on the contrary something that has the values of art is certainly beautiful. This view causes overlapping descriptions of art meanings. Accordingly, art and beauty often replace each other in the world of art. The question is then about the meaning of art and of beauty, and its forms and shapes. To create an art work, it is impossible to neglect materials that form it. An art work is physical but the shape itself is not necessarily regarded as art. Whether a physical shape has art values depends on the values inside. These inner values, the so-called art content values, are the first to catch by art appreciators and lovers. In comprehending an art work, the Forms of Fashion Base and the Form and Content in the Fashion Work is applicable to analyse an art's form and conent. Key words: art, form and content